2005
DOI: 10.1111/j.1442-2042.2005.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic recurrence in stage I seminoma: A new phenomenon that questions modern protocols for radiotherapy and follow‐up

Abstract: Objective : To highlight the increased risk for pelvic relapse in patients with stage 1 seminoma treated with adjuvant radiotherapy limited to para-aortic template alone. Patients and methods : Over a four-year period, three patients presented with early pelvic recurrence after radical orchidectomy and adjuvant irradiation for stage 1 seminoma. In each case, radiotherapy had been limited to the para-aortic region with omission of the ipsilateral hemi pelvis.Results : Pelvic recurrences occurred on the ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The reduced volume permits limiting the area, preserving the remaining testicular function and will hopefully decrease the secondary cancer rate [40,41]. However this strategy is still debated [42] in spite of the very well conducted randomized study by the Medical Research Council (MRC) Testicular Cancer Working Party. In this trial 478 patients were randomized between para-aortic and pelvic RT versus para-aortic RT alone.…”
Section: Stage I Seminomamentioning
confidence: 99%
“…The reduced volume permits limiting the area, preserving the remaining testicular function and will hopefully decrease the secondary cancer rate [40,41]. However this strategy is still debated [42] in spite of the very well conducted randomized study by the Medical Research Council (MRC) Testicular Cancer Working Party. In this trial 478 patients were randomized between para-aortic and pelvic RT versus para-aortic RT alone.…”
Section: Stage I Seminomamentioning
confidence: 99%
“… 2 Management most often involves orchidectomy with adjuvant radiotherapy, yielding excellent results with 5-year survival rates as high as 98%. 3 Studies have noted early relapse rates for stage I seminoma with adjuvant radiation or chemotherapy to be approximately 15–19% by 15 months. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Of patients that present with stage I seminoma, 15% are thought to already have micrometastases to regional lymph nodes. 3 These relapse rates warrant lifetime active surveillance with CT, especially within the first few years after initial treatment. Benefits and risks of active surveillance, such as radiation exposure and financial status of the patient should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the para-aortic field has emanated as the standard radiation approach in seminoma patients [15], Power et al [16] reported the occurrence of ipsilateral pelvic relapse in 3 patients that would otherwise have been avoided if the radiation field was extended. In our case series, one out of the 3 patients who developed relapse harbored regional disease.…”
Section: Discussionmentioning
confidence: 99%